Narrative Structure in a Novel "Ambushes of Darkness" by Fatima Al Mazrouei - Aissa, Noura; Bouali, Abderrahmane; Alhashmi, Badiae (Al-Adab Journal, 2023)
This paper presents a study of the narrative structure in the novel "Ambushes of the Dark" by Fatima Al Mazroui, and the reason behind choosing the novel "Ambushes of the Dark" is the suffering of women in the patriarchal society. This paper attempts to answer the following questions: What is meant by narrative structure? What are its elements in “Ambushes of the Dark”? How did the author employ it in her novel?The study includes an introduction, in which the researcher presented the modern novel, its methodology, and the studies that were based on the novel. The research paper is divided into three chapters. The first chapter examines the definition of structure narrative, lexically and contextually. The second chapter describes the life of the novelist and the novel, for which it won the Al Owais Award for Best Fictional. The third chapter, examines the narrative structure in “Ambushes of the Darkness” through four components: First, the event structure and its relation to the other components, then the chapter touches upon the character structure and shows its importance in the novel, then the study of the narrative place and its types in the novel, finally the structure of time and its importance.